Nathusius’ bats, Pipistrellus nathusii, bypass mating opportunities of their own species, but respond to foraging heterospecifics on migratory transit flights - Marggraf, Lara C.; Lindecke, Oliver; Voigt, Christian C.; Pētersons, Gunārs; Voigt-Heucke, Silke L. (Frontiers in Ecology and Evolution, 2023)
In late summer, migratory bats of the temperate zone face the challenge of accomplishing two energy-demanding tasks almost at the same time: migration and mating. Both require information and involve search efforts, such as localizing prey or finding potential mates. In non-migrating bat species, playback studies showed that listening to vocalizations of other bats, both con-and heterospecifics, may help a recipient bat to find foraging patches and mating sites. However, we are still unaware of the degree to which migrating bats depend on con-or heterospecific vocalizations for identifying potential feeding or mating opportunities during nightly transit flights. Here, we investigated the vocal responses of Nathusius’ pipistrelle bats, Pipistrellus nathusii, to simulated feeding and courtship aggregations at a coastal migration corridor. We presented migrating bats either feeding buzzes or courtship calls of their own or a heterospecific migratory species, the common noctule, Nyctalus noctula. We expected that during migratory transit flights, simulated feeding opportunities would be particularly attractive to bats, as well as simulated mating opportunities which may indicate suitable roosts for a stopover. However, we found that when compared to the natural silence of both pre-and post-playback phases, bats called indifferently during the playback of conspecific feeding sounds, whereas P. nathusii echolocation call activity increased during simulated feeding of N. noctula. In contrast, the call activity of P. nathusii decreased during the playback of conspecific courtship calls, while no response could be detected when heterospecific call types were broadcasted. Our results suggest that while on migratory transits, P. nathusii circumnavigate conspecific mating aggregations, possibly to save time or to reduce the risks associated with social interactions where aggression due to territoriality might be expected. This avoidance behavior could be a result of optimization strategies by P. nathusii when performing long-distance migratory flights, and it could also explain the lack of a response to simulated conspecific feeding. However, the observed increase of activity in response to simulated feeding of N. noctula, suggests that P. nathusii individuals may be eavesdropping on other aerial hawking insectivorous species during migration, especially if these occupy a slightly different foraging niche.